Pengaruh Kesadaran Pajak, Sanksi dan Program Pemutihan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor: Studi Kasus di Kabupaten Sleman - Azzahrotul Jannah; Nugraeni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The tax is a territorial tax that must be paid. Seriousness in fulfilling tax obligations and reporting can show the level of awareness of people who are required to pay taxes. Taxpayers must carry out their responsibilities and pay carefully and on time because Indonesia has a self-evaluation system. That is the main income tax. The two-wheeled vehicle tax has the highest influence on regional income because it is a regional tax that needs to be paid. Income level is also very important and is related to a person's compliance with the tax contributions paid. This research investigates how taxpayer awareness, sanctions, and whitening programs impact motor vehicle taxpayer compliance in Sleman Regency from 2019 to 2022, with 100 respondents. Information in the form of questionnaires is usually processed and analyzed. Considering the outcomes of the hypothesis test, demonstrates vehicle tax compliance in the Sleman region in 2019–2022 is unaffected by taxpayer awareness of sanctions and whitening programs.